STUDY ON EFFECT OF IMMUNE STIMULATION OF γ-RAY IRRADIATED β-GLUCAN ON TILAPIA - NGUYEN , NGOC DUY; NGUYEN , QUOC HIEN; DANG , VAN PHU (Nuclear Science and Technology, 2013)
Low molecular weight β-glucan (LMWβG) and oligo β-glucan (oligoβG) solutions were prepared by combination of hydrothermal steaming and radiation decomposition methods. The efficiency of the degradation process was demonstrated by gel permeation chromatography (GPC) analysis of the average molecular weight (Mw) of β-glucan. Results showed that the Mw of LMWβG was decreased with increasing steaming time, concentration of H2O2 and doses of irradiation. For LMWβG, Mw reduces from 296,600 Da to 44,400 Da when concentration of H2O2 raise from 2.5% to 10% and for oligoβG Mw reduces from 40,487 to 9391 when concentration of H2O2 raise from 0.5% to 5%. OligoβG which was prepared by radiation decomposition method, the Mw decreased from 56,700 to 7145 when the dose increased from 0 to16 kGy. LMWβG and oligoß-glucan are mixed into fish food at a concentration of 100 ppm. Fish were fed a diet containing LMWβG and oligoβG during 45 days and was challenged with Strep. agalactidae bacterial to investigate immune stimulation. The results indicated that oligoβG has higher immune stimulation effect than LMWβG. The influence of various concentrations (50, 100, and 150 ppm) of oligoβG for the immune stimulation of tilapia were investigated. Results showed that survival rate of tilapia fish was the highest for oligoβG of 150 ppm.